Infertility: Exploring male and female rates and its impact on society - Eghosa Enoriomwaniha (BioScientist: The Salford Biomedicine Society Magazine, 2024)
About 8–12% of couples globally face infertility, which is defined as the inability to conceive after a year of unprotected sexual interaction. 53.2% of males and 57.3% of women in the UK who experienced infertility needed either medical treatment or professional help. A wide range of factors, from lifestyle choices to underlying medical issues are included in the aetiology of infertility. Medical, surgical, and assisted reproductive procedures are some of the various techniques needed to treat infertility even though access and cost are still major obstacles. High levels of education, economic prosperity, and access to contraception contribute to low fertility rates in developed countries by delaying birth and eventually lowering fertility rates. To improve infertility rates, policymakers, medical professionals, and the public must work together to address the issues surrounding infertility by encouraging an inclusive and equitable approach to infertility management to lower stigma in society and increase access to care.
Keywords: infertility; assisted reproductive procedures; health disparities; clinical pregnancy; primary infertility; secondary infertility; demographic patterns of infertility; inferility education; global infertility rates; male infertility; female inferility; IVF; COVID-19; psychological stress; infertility management